PENGARUH PROMOSI JABATAN DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA PEGAWAI PADA DINAS LINGKUNGAN HIDUP KABUPATEN KAMPAR - Yusup Yusup (Jurnal Riset Manajemen Indonesia, 2020)
This study aims to determine the effect of job promotion and work discipline simultaneously and partially on employee performance in the Kampar District Environmental Service. The analysis used is multiple linear regression analysis. The number of respondents in this study was 54 people. Hypothesis testing is done by the F test and t test. Based on the results of the study it can be concluded that based on simultaneous tests (together), the promotion of position and work discipline influences the work performance of employees in the Environmental Department of Kampar Regency. Based on a partial test (individual), the promotion of position and work discipline affects the work performance of employees at the Environmental Department of Kampar Regency.